2019
DOI: 10.1088/1674-1056/28/3/030301
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical control of population and entanglement for open Λ-type atoms by engineering the environment

Abstract: The exactly analytical solution for the dynamics of the dissipative Λ-type atom in the zero-temperature Lorentzian environment is presented. On this basis, we study the evolution of the population and entanglement. We find that the stable populations on the two lower levels of the Λ-type atom can be effectively adjusted by the combination of the relative decay rate and the environmental spectral frequency. However, for the initial Werner-like state, the stable entanglement between the two Λ-type atoms has very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…For instance, it has been shown that there exists a long-living entangled state due to the interaction of a two-qubit system with a common environment. [43][44][45][46][47] This idea has been generalized to an arbitrary number of qubits inside an environment. [48][49][50] Moreover, quantum reservoir engineering has been proven to be useful in stabilizing open quantum systems [51] and remote entanglement and concentration, [52] etc.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it has been shown that there exists a long-living entangled state due to the interaction of a two-qubit system with a common environment. [43][44][45][46][47] This idea has been generalized to an arbitrary number of qubits inside an environment. [48][49][50] Moreover, quantum reservoir engineering has been proven to be useful in stabilizing open quantum systems [51] and remote entanglement and concentration, [52] etc.…”
Section: Introductionmentioning
confidence: 99%